Retrospective review of dosing trends in botulinum toxin injections for the treatment of adductor spasmodic dysphonia in a long-term cohort - Gabrielle French; J. Douglas Bosch; Derrick R. Randall (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Botulinum toxin A (BT) is the gold standard treatment for adductor spasmodic dysphonia (AdSD) with established use for greater than thirty years. The spasmodic dysphonia (SD) literature would benefit from additional long-term cohort data, especially in the Canadian population. The goals of this study were to evaluate whether BT dosage required to achieve acceptable voice shifts over time and to elucidate differences in the subgroups of patients receiving unilateral vocal fold (UVF) injections. Methods Patient records were retrospectively reviewed at the regional tertiary Voice Clinic for AdSD patients from 1996 to 2017 to identify AdSD patients treated with serial BT injections. Descriptive statistics, paired t-tests for time between treatments and ANOVA tests were used to evaluate trends in subgroup age. Results One-hundred and twenty-six patients (61% female, mean age = 53 ± 15.5 years) met inclusion criteria and received laryngeal EMG-guided BT injections for up to twenty-two years and as many as 79 treatments. The mean total BT dosage for our population was 1.54 ± 0.35 Units per side. The majority of subjects had decreasing doses over time with a small subgroup having slowly increasing doses. Comparing treatment dosages between unilateral and bilateral injection groups, injection dosage per vocal fold was 1.65 ± 0.62 with time between injections was significantly shorter for the unilateral injection group (mean = 105 days, SD ± 19.8 days, p = 0.005) compared to the bilateral injection subgroup (137 ± 35.7 days, p < 0.005). The mean age of the unilateral injection population as younger at 42.4 ± 11.8 years (p = 0.004). Conclusion The majority of patients in this study had decreasing BT injection dosages over time, with a smaller proportion having slowly increasing doses, thought to be likely relating to disease severity. The unilateral vocal fold injections were well tolerated despite needing more frequent injections, and found to be more prevalent in the younger age group.